Elevation of serum SSCCAII in cutaneous and oral lichen planus: Missing link for hidden carcinogenic potential? - Nancy W Mikhael; Walid Abd El latif; Doaa M Elhabak (Wolters Kluwer Medknow Publications, 2021)
Context: Lichen planus (LP) is an immune mediated inflammatory condition. SCCAII is a useful biomarker reflecting Th17 type inflammation. It is also a tumour marker, especially for Squamous cell carcinoma (SCC) Mechanism of carcinogenesis in LP is still unknown. Chronic inflammation may facilitate the development of cellular clones in the epidermis. Aims: Estimation of serum level of SCCA II in patients with cutaneous and oral LP (OLP) to detect its role in LP pathogenesis, and to reveal the missing link in understanding mechanism of carcinogenesis in LP. Methods and Material: A case control study, where 100 subjects were included; 80 LP patients (40 cutaneous & 40 oral) and 20 apparently healthy controls. We obtained an informed written consent from each subject prior the participation. Cutaneous and oral LP were diagnosed clinically, SCCA II level was measured by ELISA technique. Statistical analysis used: Statistical analysis was done using SPSS vs.25. (IBM, Armonk, New York, United states). Numerical data was summarized as means and standard deviations or medians and ranges. Results: Median SSCCAII level was significantly higher in LP cases compared to controls (P < 0.001) and was significantly higher in patients with OLP compared to patients with cutaneous LP (P ≤ 0.001). Post hoc analysis revealed that median SSCCAII was significantly higher in patients with ulcerative type compared to both reticular type and others. It was also significantly higher in patients with actinic type compared to both hypertrophic type and classic type. Median SSCCAII was significantly higher in patients with ulcerative OLP compared to actinic LP (P < 0.001). Conclusions: Our study revealed that serum SCCAII level was higher in patients with cutaneous and OLP. This might be linked to the pathogenesis of LP, especially actinic and erosive OLP. SCCAII level could facilitate the screening and early detection of patients at risk, a potential alarm to launch accurate assessment and continue follow up of cutaneous as well as O LP patients.